The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41598-023-27425-6
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive occupancy and vital signs sensing for human building interactive systems

Abstract: Cognitive buildings use data on how occupants respond to the built environment to proactively make occupant-centric adjustments to lighting, temperature, ventilation, and other environmental parameters. However, sensors that unobtrusively and ubiquitously measure occupant responses are lacking. Here we show that Doppler-radar based sensors, which can sense small physiological motions, provide accurate occupancy detection and estimation of vital signs in challenging, realistic circumstances. Occupancy was diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The ability to monitor vital signs from various angular positions presents a significant advantage in the context of smart home applications. This advantage eliminates the necessity for individuals to be directly positioned in front of the radar system [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], which allows greater flexibility and convenience as individuals can perform their daily activities while still having their vital signs monitored. Additionally, this advantage enhances the usability and effectiveness of smart home applications in monitoring and maintaining individuals’ health and well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to monitor vital signs from various angular positions presents a significant advantage in the context of smart home applications. This advantage eliminates the necessity for individuals to be directly positioned in front of the radar system [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], which allows greater flexibility and convenience as individuals can perform their daily activities while still having their vital signs monitored. Additionally, this advantage enhances the usability and effectiveness of smart home applications in monitoring and maintaining individuals’ health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring was carried out at different distances, specifically within the range of 2 to 4 m, and at varying angles spanning from 0 to 45 degrees. In [ 22 ], a specially designed Doppler radar was utilized to identify the presence of an individual within a room and subsequently track their vital signs at periodic snapshots when the person was in different locations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that radar systems can be designed in compact monolithic packages similar to wireless telecommunications devices and can function without affecting the monitored subject ( Droitcour et al., 2001 ; Droitcour et al., 2004 ; Savage et al., 2016 ). The range of operation for low-cost, low-power Doppler radar transceivers also makes them suitable for applications beyond healthcare including occupancy detection, search and rescue, and security applications ( Park et al., 2007a ; Lubecke et al., 2007 ; Islam et al., 2023 ; Song et al., 2023 ). Off-the-shelf radar kit designs have also been used for radar sleep monitoring and automated sleep apnea detection ( Zaffaroni et al., 2009 ; Savage et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the drawbacks of traditional PIR and US sensors, new technologies, such as hybrid (combining PIR and ultrasound in one sensor) [3], infrared time-of-flight [4], video [5], CO 2 [6], thermopile array [7,8], chair sensors [9], and radar sensors [7,[10][11][12][13][14][15][16] have been in development, with some of them emerging in the market. New approaches to signal processing are also being developed to improve the accuracy of occupancy detection, reduce false-vacancy signals, and add features such as count estimation.…”
Section: Introductionmentioning
confidence: 99%
“…The installation cost, privacy concerns, lag times, or persistent inability to detect sedentary individuals has prevented sensors that can truly detect the presence of sedentary occupants from penetrating the market. However, recent developments in Doppler-radar occupancy sensing are promising because they detect breathing motion [10,12,13] and are being shown to reliably detect the presence of sedentary occupants in realistic settings [14], including in vehicle cabins [20][21][22].…”
Section: Introductionmentioning
confidence: 99%